The role of women self-help groups in reproductive health: an operational research - Amarnath, Vaishnavi Devi Moola; Jeyaraju, Anitha Rani; Iyer, Ramesh Harihara; Iyer, Ramesh Harihara (International Journal Of Community Medicine And Public Health, 2019)
Background: In India, women in the reproductive age group (15-44 years) comprise 53% of women population (according to 2011 census). In spite of continuous evolution to improve reproductive health services in India, there is insufficient progress in decline of maternal mortality rate at 2 percent per annuum. One of the innovative strategies identified in reproductive and child health (RCH) II program and UN millennium declaration was establishment of women self-help groups (SHG’s) particularly in rural regions with high levels of poverty. So this study is aimed to assess the current role of women SHG’s in, maternal health, Family welfare and associated maternity benefit schemes. And also, to find out the constraints in involvement of women SHG’s and to assess the feasibility of enhancing their role in reproductive health services. Methods: It is a population based cross sectional study carried out at Nemam sub centre area of Nemam primary health care centre under Thiruvallur housing and urban development. Women who have been a SHG member for more than 6 months were assessed quantitatively and qualitatively after obtaining informed consent which was approved by institutional ethics committee. Data was compiled and analyzed using SPSS 15.0. Qualitative data was analyzed using coding techniques. Results: A total of 56 self-help groups from 10 villages resulted in a total study population of 392 individuals. Before identifying their role, their awareness was also evaluated. Ninety percent of the SHG women were aware of most of the components of maternal health services. But the role was good among 58% of the SHG women. This study brings forth the gap in knowledge and their role which is because they were not confident of their knowledge. Conclusions: In a developing country like India, involving the well organized and available grass root volunteers like women SHG’s in reproductive health services will have a great bearing on the maternal health and consequently on health of children and community at large.